Muslim personality effects on workplace deviance : an empirrical analysis of employees working in small and medium enterprises (SMEs') - Farooq, Waqas (Centre for Strategic Continuing Education and Training, International Islamic University Malaysia, 2015)
Workplace deviant activities are the biggest menace faced by organizations today; moreover, no organization is immune to it. A significant amount of research have indicated that personality factors predict workplace deviance by using the conventional measures of personality. Researchers have neglected the spiritual and religious aspect of personality, in particular the personality characteristics as defined by Islam. In order to fill this gap in literature, the current study analyses how Muslim personality is different from the conventionally available personality models. Secondly, this research proposes and empirically tested conceptual framework that states Muslim personality dimensions, namely; rational mind (containing self-accountability, justice, truthfulness, and trustworthiness), emotional mind (containing humbleness, fear of Allah, love of Allah, and gratefulness), and social mind (containing brotherhood, self-discipline, self-sacrifice, and cooperation) have negative impact on workplace deviance (interpersonal and organizational). Data were collected from 372 employees of small and medium enterprises (SMEs) operating/registered in Kuala Lumpur, Malaysia. The results indicate that the Muslim personality model is valid for organizational behavioural research. All dimensions of Muslim personality indicate negative influence on workplace deviance. Moreover, every facet of each dimension also indicates negative effect on workplace deviance, except self-accountability and self-sacrifice. Gratefulness is only significant with interpersonal deviance. Theoretically, the study extends the contingency theory, and resource based view, and it provides empirical support for Al-Ghazali's theory of Muslim personality. There are slight differences of personality effects between manufacturing and service SMEs. The current study is of cross-sectional nature, and only direct effects of Muslim personality on workplace deviance are analysed. Therefore, future researcher may consider longitudinal study, and inclusion of situational variables as moderators in this research model, to further explore the relationship between Muslim personality characteristics and workplace deviance.